KINERJA DAN RANCANGAN PEMECAHAN MASALAH LALU LINTAS BAGIAN BARAT UTARA KOTA SEMARANG - Dhyani Ciptaning Asmara; Rini Kusuma Wardani; Epf. Eko Yulipriyono; Supriyono Supriyono (Jurnal Karya Teknik Sipil, 2014)
Semarang city is very strategic because it is located in the middle of the north track of Java, connecting East Java and West Java. Annually vehicles across the city of Semarang increases, this was the trigger traffic jams especially on road segment and intersection of the north - west Semarang city. The growth of Gross Regional Domestic Product at Constant Prices 2000 Central Java 6 percent represents that the rate of growth in daily traffic average intersection has increased in the next 5 years. Figures show the feasibility of the service with the highest degree of saturation (DS), the condition on the road DS < 0.75 and at the intersection of DS < 0.85. The results of the analysis of primary data obtained from the field survey in September until Oktober 2013 showed the value of DS on existing roads still eligible, while the value of DS intersections are not eligible. Basic steps of traffic jams problem solving,namely the optimization of intersections with signal timing, intersection geometry settings and traffic management. After these steps are considered not provide significant changes in the value of DS, the last step is planning the construction of northern outer ringroad, or toll road.With the construction of new roads, intersection capacity will be increased with increasing growth rate LHR Semarang city in the years to come.